Simulation modeling of root crop unloading from body of vehicle (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article describes the features of methodological justification of simulation modeling of unloading of root crops from the body of the vehicle. The developed model allows you to consider the large number of parameters of roots, body body, elastic tubes, unloading parameters, as well as calculate the main indicators of the efficiency of unloading of roots. The rational lumen between the elastic septum and the bottom of the body of the vehicle is 2 cm, and the rigidity of the elastic tubes for bending is 0.9 kN/m2. The unloading time will be less than 11.5 C, the rolling distance of the roots will be less than 1.50 m, the proportion of damaged roots will be less than 4.0%.
Keywords: vehicle; body; operation; root